2015
DOI: 10.1073/pnas.1423857112
|View full text |Cite
|
Sign up to set email alerts
|

Specialized insulin is used for chemical warfare by fish-hunting cone snails

Abstract: More than 100 species of venomous cone snails (genus Conus) are highly effective predators of fish. The vast majority of venom components identified and functionally characterized to date are neurotoxins specifically targeted to receptors, ion channels, and transporters in the nervous system of prey, predators, or competitors. Here we describe a venom component targeting energy metabolism, a radically different mechanism. Two fish-hunting cone snails, Conus geographus and Conus tulipa, have evolved specialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 29 publications
4
174
1
1
Order By: Relevance
“…Finally, we measured foxn3 transcripts in zebrafish injected with vehicle or streptozotocin (STZ) to gauge the rapidity of foxn3 downregulation in response to unopposed endogenous glucagon action. Twenty-four hours following a single STZ treatment, blood glucose levels were significantly increased from 67 ± 6 mg/dL to 270 ± 34 mg/dL (p < 0.01; Safavi-Hemami et al, 2015); liver foxn3 transcript abundance in these animals was decreased by STZ treatment (Figure 1F). …”
Section: Resultsmentioning
confidence: 96%
“…Finally, we measured foxn3 transcripts in zebrafish injected with vehicle or streptozotocin (STZ) to gauge the rapidity of foxn3 downregulation in response to unopposed endogenous glucagon action. Twenty-four hours following a single STZ treatment, blood glucose levels were significantly increased from 67 ± 6 mg/dL to 270 ± 34 mg/dL (p < 0.01; Safavi-Hemami et al, 2015); liver foxn3 transcript abundance in these animals was decreased by STZ treatment (Figure 1F). …”
Section: Resultsmentioning
confidence: 96%
“…Our reanalysis discovered more 'I4' superfamily sequences and reclassified these into the I2 superfamily. A closer inspection of the reported novel Y2 superfamily sequences revealed that they were also misclassified (Safavi-Hemami et al, 2015) and belonged to the recently described coninsulin class (Figure 2). The H2 superfamily described by Lavergne et al comprised one transcript with a single read that was identical to the peptide Mr3.8 belonging to the M superfamily with the exception of the first few residues of the reported signal sequence .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 92%
“…Though this program can handle large datasets, an overreliance on such programs can miss novel toxin sequences that frequently possess novel cysteine scaffolds. It can also lead to incorrect annotations, such as the Coninsulins from Conus geographus being misidentified as a novel conotoxin gene superfamily (Safavi-Hemami et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…2000 platform at Cofactor Genomics as described previously (Safavi-Hemami et al, 2015). Reads were de novo assembled using Trinity (Grabherr et al, 2011) and annotated using BLASTx.…”
Section: Methodsmentioning
confidence: 99%
“…Examples include the conopressins (vasopressin analogues) from Conus geographus and Conus striatus (Cruz et al, 1987), contulakin-G (a neurotensin analogue) from C. geographus (Craig et al, 1999), RFamide neuropeptides from Conus spurius and Conus victoriae (Maillo et al, 2002; Robinson et al, 2015), conomap (a myoactive tetradecapeptide) from Conus vitulinus (Dutertre et al, 2006), conoCAPs (analogues of crustacean cardioactive peptide) from Conus villepinii (Möller et al, 2010) and neuropeptide-F/Y from Conus betulinus (Wu et al, 2010). Furthermore, we recently demonstrated that specialised insulins are an abundant and active component of some Conus venoms (Safavi-Hemami et al, 2015). When injected into fish, the venom insulin elicits hypoglycemic shock, thus facilitating capture of the physiologically impaired prey.…”
Section: Introductionmentioning
confidence: 99%